Gênese e controle dos depósitos hematíticos-magnetíticos encaixados no Complexo Guanhães - Flávia Cristina Silveira Braga (2019)
Horto-Baratinha (HBD) and Cuité (CTE) high-grade iron ore deposits (>60% wt. Fe) are located at the eastern margin of the São Francisco Craton, western part of the Araçuaí Orogenic Belt. The high-grade bodies are hosted in metamorphosed iron formation (itabirite) associated with paraderived mica schists and amphibole schist of amphibole facies and Statherian maximum deposition age, enclosed by Statherian granitoids of the Borrachudos Suite and Neoarchean gneiss of the Guanhães Complex. Pegmatitic bodies with crystallization age of 560 to 490 Ma crosscut all units. The metasedimentary sequence is correlated with the Orosirian-Statherian Serra da Serpentina and Serra de São José Groups (basal unit of the Espinhaço Supergroup). The iron formation was deformed during the Brasiliano Orogeny, and the banded structure is transposed by an axial planar schistosity, defined by lamellar hematite and quartz, enveloping high-grade ore lenses. The country rocks in HBD have undergone at least three stages of deformation making up a dome and basin deposit-scale refolding shape. The CTE sequence undergone a transpressive deformation generating shear zones and SE-verging thrust faults. Three high-grade iron ore facies were identified, granular hematitic ore with magnetite idioblasts, which is the predominant facies in both deposits, and secondary lamellar-granular hematitic ore and magnetitic ore lenses. The whole-rock REE+Y data of the itabirite are very similar to platformal (Lake Superior) iron formations with an overall low abundance of detrital components. The texture and the microchemical composition of the iron oxides identified in itabirite, iron ore, and pegmatite indicate three mineralization phases. (1) The metamorphic recrystallization and transposition of the sedimentary structures, Si-leaching along shear zones and crystallization of lamellar hematite during the syn-collisional and late-collisional stages (580 - 560 Ma) of the Brasiliano Orogeny. (2) Partial melting of the Borrachudos granite during the late-collisional and post-collisional/gravitational collapse of the orogeny (560 - ~530 Ma). During this phase, high-temperature fluids from pegmatite interacted with country rocks, resulting in the formation of kenomagnetite and Si-leaching. (3) During the final stage of gravitational collapse (~530 - 490 Ma), when the sequence was uplifted, the mixing between meteoric and magmatic fluids promoted the oxidation of kenomagnetite to martite and granular hematite. The general similar composition between the iron oxides from ore and pegmatite indicates their closely related origin. Titanium and Mn were mobile during the metasomatic high fluid/rock interactions, generating Mn-rich magnetite and Ti-rich hematite. Zircons from metasedimentary rocks, granite, and gneiss suffered recrystallization at sub-solidus conditions, due to the interaction with hydrothermal fluids affecting their chemical and isotopic composition. Keywords: Brasiliano hydrothermalism, iron ore, Guanhães Block, metalogenesis, geochemistry.